Relationship between hippocampal atrophy and neuropathology markers: A 7T MRI validation study of the EADC‐ADNI Harmonized Hippocampal Segmentation Protocol. Issue 2 (22nd January 2015) - Apostolova, Liana G.; Zarow, Chris; Biado, Kristina; Hurtz, Sona; Boccardi, Marina; Somme, Johanne; Honarpisheh, Hedieh; Blanken, Anna E.; Brook, Jenny; Tung, Spencer; Kraft, Emily; Lo, Darrick; et al.
Abstract: Objective: The pathologic validation of European Alzheimer's Disease Consortium Alzheimer's Disease Neuroimaging Initiative Center Harmonized Hippocampal Segmentation Protocol (HarP). Methods: Temporal lobes of nine Alzheimer's disease (AD) and seven cognitively normal subjects were scanned post‐mortem at 7 Tesla. Hippocampal volumes were obtained with HarP. Six‐micrometer‐thick hippocampal slices were stained for amyloid beta (Aβ), tau, and cresyl violet. Hippocampal subfields were manually traced. Neuronal counts, Aβ, and tau burden for each hippocampal subfield were obtained. Results: We found significant correlations between hippocampal volume and Braak and Braak staging (ρ = −0.75, P = .001), tau (ρ = −0.53, P = .034), Aβ burden (ρ = −0.61, P = .012), and neuronal count (ρ = 0.77, P < .001). Exploratory subfield‐wise significant associations were found for Aβ in Cornu Ammonis (CA)1 (ρ = −0.58, P = .019) and subiculum (ρ = −0.75, P = .001), tau in CA2 (ρ = −0.59, P = .016), and CA3 (ρ = −0.5, P = .047), and neuronal count in CA1 (ρ = 0.55, P = .028), CA3 (ρ = 0.65, P = .006), and CA4 (ρ = 0.76, P = .001). Conclusions: The observed associations provide pathological confirmation of hippocampal morphometry as a valid biomarker for AD and pathologic validation of HarP.